Does an empathic pre-visit conversation with another team member improve perceived surgeon empathy? - Lindy Derkzen; Janna Ottenhoff; Carrie Barron; David Ring (The Beryl Institute, 2020)
Orthopedic surgeon specialists can help alleviate symptoms and reduce self-reported activity limitations by addressing stress, distress, and unhelpful cognitive biases regarding pain (e.g., "hurt equals harm"). But noticing mental and social health opportunities in specialty care can harm the patient-surgeon relationship. This study evaluated the ability of an empathic pre-visit conversation by another team member to improve the patient-surgeon relationship measured as perceived empathy. Factors associated with pain intensity, magnitude of self-reported activity limitations, symptoms of depression, and satisfaction with the surgeon were also studied. We enrolled 100 patients visiting an orthopedic surgeon for the first time. Prior to the visit with the surgeon, 50 patients met with another team member and had a pre-visit discussion about a sense of purpose and meaning in life, availability of loving relationships, and things that elicit laughter-a discussion intended to honor what matters most to an individual-and the other 50 patients did not. At the end of the visit we recorded perceived surgeon empathy, pain intensity, magnitude of self-reported activity limitations, symptoms of depression, and satisfaction with the surgeon. The pre-visit discussion did not affect perceived surgeon empathy (p=0.81), pain intensity (p=0.75), magnitude of self-reported activity limitations (p=0.63), symptoms of depression (p=0.46), or satisfaction with the surgeon (p=0.79). Patient experience with a surgeon does not benefit from a positive milieu created by a non-surgeon team member. Future studies can address relationship-building tactics used by the surgeon. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.